(untitled) (Journal of Social Sciences Review, 2023)
The central object of this research study was to find out the roots of the increasing number of street children in major urban cities of Indonesia. This research planned to find out the extent of poverty; domestic violence, family dysfunction, and wanted for freedom have increased the number of street children. The survey strategy used in this research, researchers used a survey strategy, the study target population consisted of street children working and living on the street. The interview and close-ended Questionnaire were used in this study to gather data from the respondents and out of three hundred and eighty-four (384) who were sampled three hundred eighty-one (381) of them responded, the total response rate was ninety-nine (99) percent. Descriptive and inferential statistics were used for Data analysis. The research findings established that poverty, economic deprivation, low of home, domestic violence at home by parents, and family dysfunction have generally had an impact on street children. The former street children face difficulties and isolation due to stigma.